Pemahaman Konsep Kematian dan Kecemasan Terhadap Kematian pada Remaja - Kornelia Larasati Suhardi; Julia S. Chandra (Jurnal Ilmiah Psikologi MIND SET, 2011)
A research about the death concept understanding on teenagers is still rarely held in Indonesia. Moreover, there was assumption that teenagers rarely think about death that happened to people around them or to themselves. In this explorative research, the researcher wanted to see the concept of death that the teenagers have the anxiety over death, and how the concept of death they understood related with their anxiety over their own death. The participants of this research are 180 teenagers aged 15-22 years old in Indonesia, especially those who live in Jakarta. There are two measuring tools in this research. Measuring tool for death concept was made based on five dimensions developed by Slaughter (2007) and the measuring tool for death anxiety was developed by Asri, Imanuel, Dotulong, Pratesianingrum, Putri N.W., Putri U.S., and Ramadion (2008). Based on the result of this research, it was found that the teenagers have already had a lot of death concepts even though they haven't completely got all dimensions. Teenagers' understanding on death was related with their religion and culture point of view. Besides, the anxiety in death in teenagers was adequately high. There was no relation between death concept and death anxiety. It was shown by the correlation result Pearson about 0.052. The implication of this result and suggestion is in education on death concept for children and teenagers.